2011
DOI: 10.1093/cid/cir919
|View full text |Cite
|
Sign up to set email alerts
|

Household Versus Individual Approaches to Eradication of Community-Associated Staphylococcus aureus in Children: A Randomized Trial

Abstract: NCT00731783.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 43 publications
7
148
0
Order By: Relevance
“…24 More recently, community studies from the US have shown decolonisation may reduce the risk of recurrent boils and abscesses, particularly when an entire household is treated simultaneously. 14,15 However there is little consensus on how decolonisation should be undertaken in the community or how to manage patients with recurrent boils who remain persistently colonised despite treatment.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…24 More recently, community studies from the US have shown decolonisation may reduce the risk of recurrent boils and abscesses, particularly when an entire household is treated simultaneously. 14,15 However there is little consensus on how decolonisation should be undertaken in the community or how to manage patients with recurrent boils who remain persistently colonised despite treatment.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…12,13 However, the effectiveness of such interventions is questionable and they are resource intensive. 14,15 There is a clear need for guidance on how to manage patients with recurrent disease in the community. The aim of this study was to determine the burden of recurrent disease and identify opportunities for secondary prevention in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent was obtained at study enrollment for cases and household contacts. Patients aged 6 months to 20 years with SSTI were screened from May 2008 to December 2009 from the Emergency Department and ambulatory wound center of St Louis Children's Hospital (SLCH) and from 9 community pediatric practices affiliated with a practice-based research network in metropolitan St Louis, MO [22]. Patients with traditional healthcare-associated S aureus risk factors (indwelling catheter or percutaneous medical device, post-operative wound infection, on dialysis, or residence in a long-term care facility) were excluded from screening.…”
Section: Study Design and Participant Recruitmentmentioning
confidence: 99%
“…Patients with traditional healthcare-associated S aureus risk factors (indwelling catheter or percutaneous medical device, post-operative wound infection, on dialysis, or residence in a long-term care facility) were excluded from screening. To detect colonization of cases, culture swabs (BBL Liquid Stuart; Becton Dickinson, Sparks, MD) were obtained at the time of screening from the anterior nares, axillae, and inguinal folds as described previously [22,23]. To confirm the presence of an S aureus infection, wound culture results were obtained from the SLCH microbiology laboratory or the relevant provider's office.…”
Section: Study Design and Participant Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation